2020
DOI: 10.1128/aac.01415-19
|View full text |Cite
|
Sign up to set email alerts
|

High Heterogeneity of Multidrug-Resistant Enterobacteriaceae Fecal Levels in Hospitalized Patients Is Partially Driven by Intravenous β-Lactams

Abstract: Multidrug-resistant Enterobacteriaceae (MRE) colonize the intestine asymptomatically from where they can breach into the bloodstream and cause life-threatening infections, especially in heavily colonized patients. Despite the clinical relevance of MRE colonization levels, we know little about how they vary in hospitalized patients and the clinical factors that determine those levels. Here, we conducted one of the largest studies of MRE fecal levels by tracking longitudinally 133 acute leukemia patients and mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Therefore, ALP represent an optimal population to study how changes in the microbiota influence MRE intestinal colonization in humans. We reported that 60% of ALP from our cohort harbor detectable levels of MRE 17 . Moreover, we found that fecal MRE levels change considerably between different patients and within the same patient over time 17 .…”
Section: Resultsmentioning
confidence: 57%
See 4 more Smart Citations
“…Therefore, ALP represent an optimal population to study how changes in the microbiota influence MRE intestinal colonization in humans. We reported that 60% of ALP from our cohort harbor detectable levels of MRE 17 . Moreover, we found that fecal MRE levels change considerably between different patients and within the same patient over time 17 .…”
Section: Resultsmentioning
confidence: 57%
“…We reported that 60% of ALP from our cohort harbor detectable levels of MRE 17 . Moreover, we found that fecal MRE levels change considerably between different patients and within the same patient over time 17 . An example of these changes is reflected in Fig.…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations